Financing social security - Campbell, Colin Dearborn; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute for Public Policy Research, 1979)
This is a conference publication by the American Enterprise Institute for Public Policy Research. The conference is divided into four sessions. The first session is on- Indexing Social Security: What to do? The second session- Indexing Social Security: Some important consequences. The third session- The Future Financing of the Social Security System. The fourth session- Interaction of Social Security and Private Pensions. Three important topics discussed at the conference are the current size of social security benefits, the nature of the alternative benefit formulas and indexing proposals, and the relative advantages and disadvantages of wage indexing as compared with price indexing.
Papers presented at a conference sponsored by the American Enterprise Institute for Public Policy Research, held in Washington, D.C., Oct. 27 and 28, 1977.
Includes bibliographical references.
ne 4/05/2018
Loans
Keywords: Social Security; Financing - social security